College student mental health and wellness : coping on campus - Hayes, Jeffrey A. (Emerald Publishing Limited, 2024)
Recent data indicates that the psychological distress of college students is on the rise. College students are increasingly culturally diverse and psychological distress in some areas is greater for minoritized students. College Student Mental Health and Wellness addresses this phenomenon that has been referred to in the popular media as the 'college mental health crisis' in a comprehensive and data-driven way. Jeffrey A. Hayes moves us forward in our understanding of these issues so that we might more effectively work with our students and those who support them. Chapters cover theories of college student development and common psychological problems among college students (including anxiety, depression and substance abuse), and important aspects of college student well-being (such as identity, peer relationships and career preparedness). Drawing on a large amount of data collected from both students in the general population as well as those seeking mental health services at U.S. colleges and universities, College Student Mental Health and Wellness illuminates the types of distress on the rise, the potential underpinnings of this distress and how administrators, educators, mental health professionals and others might better understand and work with these issues.